FEATURES OF THE DEVELOPMENT OF THE DOMESTIC INSURANCE MARKET AS A COMPONENT OF THE FINANCIAL MARKET. DIRECTIONS OF ACTIVATION OF INSURANCE ACTIVITY IN THE CONDITIONS OF FORMATION OF THE DIGITAL ECONOMY - СHEREP OLEXANDER; KHMELKOVSKIA, ANN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Insurance is one of the branches of the financial market that is more inclined to traditional ways of doing business and has a slow pace of technological innovation. However, the COVID-19 pandemic had a significant impact on the development of the insurance industry in the direction of its digitalization and increase investment in the process of innovation in the insurance market. According to the latest trends, 2021 is considered a record year for the innovative activity of the insurance industry, which has been faced with a number of challenges due to the global pandemic and awareness of the priority of digital transformation. The article is devoted to identifying current trends in insurance business innovation in the digital economy. The key technological trends of 2021 and how they are integrated into the sectors of health and life insurance, motor insurance and property insurance are studied. The stages of development of modern insurance technologies (InsurTech), which are innovative products in the insurance sector of financial infrastructure, are presented. Tools for digitalization of business processes of selling insurance products, accounting and tax accounting, risk underwriting, document management are presented. The main reasons for the reduction in the number of insurance companies in the domestic insurance market have been identified. It is determined that in the conditions of digital development it is appropriate for domestic insurance companies to implement such areas of activity as: customer-oriented approach, search for partners in the field of technology, protection of intellectual property.